Self-efficacy in communication and employability skills of English language students - Joerene Mae Layagan (Universitas Negeri Semarang, 2024)
The majority of the relevant studies have concentrated on identifying the potential employable abilities of Bachelor of Arts in English Language (BAEL) students in general rather than the employability skills of BA English Language graduates. Hence, it is important to know also what are the employable skills of the BAEL graduates in order to determine the areas of workplace they are to be employed in. This study aims to know the self-efficacy of BAEL students in oral, written, computer-mediated communication and the important employability skills of BAEL undergraduate students. The study is quantitative in nature, and a descriptive survey approach was employed to ascertain the respondents' employability skills in the various fields. The researcher used Google Forms for the survey questionnaire. The study revealed that the self-efficacy of the BA English Language fourth year undergraduate students had a positive opinion of their own skill efficacy. The English language students can handle themselves in company especially when interacting in small groups. They can carry out written communication tasks and also electronically assisted tasks. On the other hand, BAEL students have potentials to be employed in various industries. The researcher advised the students to be readily accepted in various fields in the workplace after graduation. Teachers and curriculum/policy makers were suggested to create learning interventions that can enhance the employability of the students in the various areas of English communication.